Ecological design inventing the future - Danitz, Brian; Tzelovanikov (Canada : Filmwest Associates, 1994)
An educational documentary film which illuminates the emergence of ecological design in the 20th century. The film features, the ideas and prototypes of pioneering designers who have trail-blazed the development of sustainable architecture, cities, energy systems, transport and industry.
Editor, Patricia Streeten ; music, David Darling
Narrator, Linda Hunt
Keywords: Environmental policy; Human ecology